(Technically) Difficult colonoscope insertion – Tips and tricks. Issue 5 (10th July 2019) - Rodrigues‐Pinto, Eduardo; Ferreira‐Silva, Joel; Macedo, Guilherme; Rex, Douglas K.
Abstract : Cecal intubation is a critical aspect of effective, complete colonoscopy. Difficult colonoscopy is most often considered as one in which it is challenging or impossible to reach the cecum. It may be a common occurrence due to patient and/or endoscopist factors. Incomplete colonoscopies should be avoided, since patients in this context present an important prevalence of lesions that escape examination. The approach to successful cecal intubation should depend on characterization of the problem as redundant colon or difficult sigmoid colon. Most patients with a prior incomplete colonoscopy can be colonoscoped successfully, if careful attention is paid to technique, using a variety of scopes, colonoscopy methods and additional equipment. Sufficient time should be allotted to make the attempt.